Baked egg food challenges – clinical utility of skin test to baked egg and ovomucoid in children with egg allergy. Issue 10 (16th September 2013) - Tan, J. W.‐L.; Campbell, D. E.; Turner, P. J.; Kakakios, A.; Wong, M.; Mehr, S.; Joshi, P.
Summary Background Many children with IgE‐mediated egg allergy can tolerate products containing extensively heated (baked) egg. Aside from food challenge, there are no tests which reliably predict tolerance to baked egg in egg‐allergic individuals. Objectives To determine if skin prick test (SPT) to baked egg (muffin) and ovomucoid can predict the outcome of baked egg challenges in egg allergic patients. Methods In this prospective study, children with a recent history of immediate allergic reactions to egg [and corroborative positive SPT or serum‐specific IgE (ssIgE) to egg] or those with SPT/ssIgE > 95% PPV for egg allergy were invited to undergo an open standardized baked egg (muffin) challenge. SPT to egg white, ovomucoid, and fresh muffin were performed immediately prior to challenge. Results One hundred and forty‐three egg allergic children underwent baked egg challenge and of these, 90 (63%) tolerated 1 g of egg protein in a baked muffin. Of the 53 positive challenges, eight (15%) had respiratory and/or cardiovascular symptoms. The median SPT diameters in positive challenges compared with negative challenges were baked muffin – 6.0 mm/4.0 mm and ovomucoid 7.5 mm/5.0 mm respectively. Receiver operating characteristic (ROC) curves were generated for SPT to baked egg and ovomucoid. The area under the curve was 0.68 for baked egg, and 0.67 for ovomucoid. A muffin SPT of < 2 mm had a negative predictive value of 88% and an ovomucoid SPT ≥ 11 mm had a positive predictive value of 100%. Conclusions and Clinical Relevance A SPT of < 2 mm to muffin had a high negative predictive value to baked egg challenge. Ovomucoid SPT ≥ 11 mm was very likely to predict a reaction to baked egg. In these children, deferring the challenge would be appropriate.